Роль ацетилхолина в модуляции активности нейронов неокортекса бодрствующего животного при реализации инструментального условного рефлекса - Сторожук, В.М. (Нейрофизиология, 2009)
Исследованы модулирующие влияния холинергической системы на активность нейронов сенсомоторной коры, связанную с осуществлением инструментального условного рефлекса постановки лапы на опору. Досліджені модулюючі впливи холінергічної системи на активність нейронів сенсомоторної кори, пов’язану із здійсненням інструментального умовного рефлексу постановки лапи на опору. We studied modulatory effects of the cholinergic system on the activity of sensorimotor cortex neurons related to realization of an instrumental conditioned placing reflex. Experiments were carried out on awake cats; multibarrel glass microelectrodes were used for extracellular recording of impulse activity of neurons in the sensorimotor cortex and iontophoretic application of synaptically active agents within the recording region. The background and reflex-related activity was recorded in the course of realization of conditioned movements, and then changes of spiking induced by applications of the testing substances were examined.